Mechanical Properties of Alkali-Treated Carica Papaya Fiber-Reinforced Epoxy Composites. Issue 1 (2nd January 2022) - kumaar, A. Saravana; Senthilkumar, A.; Saravanakumar, S. S.; Senthamaraikannan, P.; Loganathan, L.; Muthu Chozha Rajan, B.
ABSTRACT: This investigation aimed at finding the effect of weight fraction (10 wt.%, 20 wt.% and 30 wt.%) and fiber orientation (0°, 45° and 90°) on mechanical properties (Tensile, Flexural and Impact) of Carica papaya fiber/epoxy (CPFE) composite. Totally nine composite samples were fabricated by hand layup followed by compression molding method. Testing results revealed that composites containing 20 wt.% and 0° fiber orientation exhibited better mechanical properties such as tensile strength (122 MPa), flexural strength (118.9 MPa) and impact strength (7.8 J) when compared to composite samples with other weight fraction and orientation. The scanning electron microscope (SEM) analysis was used to analyze the fractured surfaces of the composite specimens. The thermal stability of CPFE composites was evaluated by the Thermo Gravimetric (TG) and Differential Thermo Gravimetric (DTG) curves. All the findings led to the conclusion that the CPFE composites are suitable material to make the light weight industrial applications.